The impact of export performance resources of companies belonging to clusters: a study in the French winery industry - Zen, Aurora Carneiro; Fensterseifer, Jaime Evaldo; Prévot, Frédéric (Review of Business Management, 2014)
The purpose of this paper was to analyze the impact of resources on export performance of clustered companies. We argue that the insertion in clusters provides access to resources that influence the internationalization process of firms. We conducted a survey in the French wine industry, the main consumer market in volume and second largest producer of wine in the world. The population of the study includes exporting French wineries, located in clusters. The sample consists of 130 French wine exporters, located in different wine clusters. In short, the results indicated that access to cluster’s resources has a positive impact on the process of internationalization and export performance of companies. One managerial implication of the research is the importance of commercial resources. The firms with higher export performance attributed greater importance to their commercial resources. Further studies may measure the utilization of resources in the internationalization strategy, and compare the importance and the use of resources in accordance with the level of export performance of companies.